Soil-Derived Endospore-Forming Bacillus Bacteria Producing Protease - Mazidah Noer Inayah; Suci Indah Budiarti; Rizal Khoirun Alfisah (JRST (Jurnal Riset Sains dan Teknologi), 2025)
Proteases are widely utilized in many industries, including waste treatment, textiles, detergents, food processing, and medicines. This encourages researchers to discover novel sources of these enzymes. Exploration and isolation of putative proteolytic bacteria from the soil is one promising approach. The purpose of this study is expected providing the bacterial isolates that will produce superior proteases. Proteolytic bacteria were isolated from soil samples using the spread plate technique and selective skim milk agar media. The formation of clear zones and the determination of the proteolytic index were the starting point for a qualitative analysis of protease activity. Protease activity was determined quantitatively. The substrate is 1% casein dissolved in a 0.2 M tris-HCl buffer at pH 7.5, while the standard is tyrosine. The quantitative measurement of protease activity was carried out concurrently with the bacterial growth curve determination. The proteolytic bacteria P02 was successfully isolated in this research, having a protease enzyme activity of 0.867 U/mL and a proteolytic index of 0.8 ± 0.1. Protease activity peaked when the bacterial growth was in the logarithmic phase. Proteolytic bacterial P02 was Gram-positive and possesses the ability to form endospores and has a rod-shaped cell morphology. According to the outcomes of biochemical physiological testing, the bacterial P02 is considered to be the genus of Bacillus sp. The proteolytic bacteria P02 has potential to provide a sustainable and renewable source of protease, which is widely employed in industry and biotechnology.